Cara Guru Ngaji Dalam Meningkatkan Membaca Al-Qur’an Majelis Taklim Aisyiyah Kabupaten Seluma - Riza Jayanti; Sofino Sofino; Agus Rahmat (Jurnal Pendidikan Sepanjang Hayat, 2020)
The research is aimed to describe the eforts of reciting Al-Quran teacher in increasing reading Al-Quran ability of women of taklim souncil Aisiyah RT 03 at Masmambang village Talo Subdistrict Seluma Regency. Subjects in this research are the chief and reciting Al-Quran teacher of Taklim Souncil Aisiyah, and 2 studying citizens of Taklim Souncil Aisiyag. Technique of collecting the data uses interview, observation, and documentation. Analyzing the data is done with these following steps: data reduction, data presentation, and drawing conclusion. Validation of the data uses triangulation technique, begin from subject triangulation, time triangulation, and technique triangulation. The result of the research shows that method that is used by  Mrs. Sampurna as reciting Al-Quran teacher of Taklim Souncil Aisiyah is Iqra’ Method in which by this method, it can help Mrs. Sampurna in doing teaching and learning process of reciting Al-Quran at Aisyah Shelter. The implementation is reciting Al-Quran directly by turns. If there is wrong reading, it will be admonished by the teacher and is corrected the reads directly and with method and the implementation which Mrs. Sampurna does gets good responds from women of Taklim Souncil Aisiyah after they end Al-Quran. They are taught Tajwid understanding , if there is reciting from another place , they also follow the reciting in order to improving the ability of reciting Al-Quran  too. The infrastructures at Taklim Souncil Aisiyah are still suitable and enough to facilitate women of Taklim Souncil Aisiyah. The proponent factor of Mrs. Sampurna as reciting Al-Quran teacher of Taklim Souncil Aisiyah and Mrs. Sukarsih and also Ibu Rusni is the wants and big spirit for studying of reciting Al-Quran and the obstacle factor is the infrastructure which is the building of shelter as the place of women of taklim souncil Aisiyah for studying the Alquran reciting has been brittle and broken. Keywords: reciting Al-Quran teacher, effort, Taklim Souncil, reading Al-Quran